E-SERVQUAL BAKRIE UNIVERSITY ACADEMIC ADMINISTRATION BUREAU USING IMPORTANCE PERFORMANCE ANALISYS - Cindy Ladipa Kirana; Bambang Purwoko Kusumo Bintoro (Jurnal Scientia, 2023)
This research was conducted to determine whether there is an influence of the E-Service Quality variable BAA on student satisfaction. As for the objects in this study are the active students of Bakrie University for the odd period 2020/2021 semester 5, 7 and 9 for all majors. The E-Service Quality variables used in this study were Ease of Use & Aesthetic, Responsiveness, Realibility, Information and Security, using the IPA (Importance Performance Analysis) method. The results showed that based on the results of the level of conformity (TKi) showed that the performance given by BAA was good enough but did not fully fulfill the interests in accordance with student expectations. Based on the Importance Performance Analysis diagram, there are three attributes that are the main priority for improvement, namely Aesthetic or Ease of Use - ease of use of online service systems, information or delivery of information and reliability - reliability of BAA employees. For the Gap value or gap <-1, the average overall value obtained is -0.20. This value reflects that the performance of academic administration services has not been able to meet the overall level of student satisfaction, in other words the Academic Administration Bureau services perform quite well significantly, but for several attributes, namely the dimensions of responsiveness and the dimensions of information need to be improved immediately Suggestions for the next research are to add friendliness variables in online services because in this study found unfriendliness in BAA online services.